Extraction of Mandibular Second Molar In A Former Drug Users, Alcohol Consumers, and Active Smokers - Kusumastiwi, Pipiet Okti; Ardlina, Syifa’ (Fakultas Kedokteran Gigi Universitas Prof. Dr. Moestopo (Beragama), 2025)
Background: Extraction of Mandibular Second Molar Extraction in Former Drug Users, Alcohol Consumers, and Active Smoker has a high risk of complications. Case report and case treatment: A 34-year-old male presented with a non-restorable carious lesion on the lower right second molar (tooth 47) and requested extraction. The patient reported poor oral hygiene, active smoking, alcohol consumption, and a prior history of chlorpromazine abuse. The extraction was performed under Inferior Alveolar Nerve Block (IANB) using Lidocaine. Anesthesia lasted approximately one hour, after which pain resumed. Post-extraction healing was monitored over two months, during which the socket of tooth 47 showed delayed epithelial closure. Discussions: Alpha-adrenergic receptor blockade from chlorpromazine, hepatic cytochrome P450 enzyme alterations due to alcohol, systemic acidosis, and post-operative smoking are known to influence the efficacy of local anesthesia and impair healing. Nicotine-induced vasoconstriction and xerostomia further disrupt tissue regeneration. Despite the absence of acute complications, socket healing remained incomplete at 8 weeks post-extraction. Conclusion: This case emphasizes the importance of evaluating systemic and behavioral risk factors before extraction.